Composition, structure and pattern of helminth assemblages associated with central European herons (Ardeidae) - Sitko, Jiljí; Heneberg, Petr (Parasitology international, 2015)
Helminths parasitizing the ardeid birds are poorly understood, and the majority of studies are limited to checklists and records of novel host-parasite interactions. Here we analyzed the prevalence, intensity and diversity of the helminth component communities associated with an extensive cohort of the five most common Czech herons (Ardea cinerea, Ardea alba, Nycticorax nycticorax, Botaurus stellaris and Ixobrychus minutus) collected in the years 1962-2013. Comparison with Ukrainian datasets supports the existence of local helminth component communities, subject to strong geographic variation. The diversity of the component communities ranged between 37.3±9.6 (A. cinerea) and 2.5±1.1 (I. minutus) species. Similarly, the frequency of particular helminths differed by over one order of magnitude, whereas the helminth load differed by over two orders of magnitude. Typically, the dominant species (Echinochasmus beleocephalus, Uroproctepisthmium bursicola, Posthodiplostomum cuticola, Apharyngostrigea cornu, Desmidocercella numidica and Neogryporhynchus cheilancristrotus) were considered local, with intermediate host species available onsite, as represented by freshwater mollusks. Of the digeneans, 52% of the species likely infected their definitive hosts outside the study area, frequently utilizing invertebrates of salt or brackish waters. For A. cinerea, the largest number of species was in adult males; however the helminth load of the adults was lower than in their juvenile counterparts. This study provides the first systematically collected evidence for the intra-annual changes of the helminth assemblages in herons.
Keywords: Helminths; Československo; Czechoslovakia; Trematodes; Migratory birds; zvířata; Biodiversity; ženské pohlaví; Bird Diseases; helmintózy zvířat; Female; Helminthiasis, Animal; mužské pohlaví; Host-Parasite Interactions; Birds; interakce hostitele a parazita; nemoci ptáků; Cestodes; biodiverzita; ptáci; Parasitic worms; Prevalence; Nematodes; Animals; Male; cizopasní červi; prevalence; Intra-annual variation